CO2 Adsorption over Zinc Oxide Impregnated NaZSM-5 Synthesized Using Rice Husk Ash - Hemalatha, Pushparaj; Palanichamy, Muthaihpillai; Murugesan, Velayutham; Kwon, Soon-Bark; Park, Duckshin; Cho, Youngmin; Tae Jang, Hyun (Asian Journal of Chemistry, 2011)
Zinc oxide (5, 10 and 15 wt %) impregnated NaZSM-5 zeolite synthesized using rice husk ash as silica source was tested for CO2 adsorption. The materials were characterized by X-ray diffraction, scanning electron microscopy, energy dispersive X-ray analysis, CO2-temperature programmed desorption and Brunauer-Emmett-Teller techniques. The heat of the reaction (DHr) derived from differential scanning calorimetry analysis for NaZSM-5 (10 %) to be 495 Btu/Lb. The maximum CO2 adsorption capacity of NaZSM-5 (10 %) is 140 mg/g of sorbent. Extraction of silica from the agricultural waste, rice husk and its use in the zeolite synthesis is an added advantage in this study. Hence, from the study it is concluded that zinc oxide impregnated NaZSM-5 could be treated as novel material for CO2 adsorption as they were found to be regenerable, selective and recyclable.